Perlindungan Hukum Korban Begal Dalam Upaya Pembelaan Terpaksa Di Tinjau Berdasarkan Pasal 49 KUHP - Fauziah, Anisa; Ananta Putra, Yudha; Mulyanto, Edy (Prodi Hukum S1 - Fakultas Hukum - Universitas Pamulang, 2024)
Not everyone who becomes a victim Robbery is silent and resigned. There are also victims of robbery who make every effort to defend themselves, their property, their honor, and their lives. In an effort to protect himself, someone who fights back by attacking the perpetrator who tries to take his property is a form of defense from someone under compulsion or in the Criminal Code is known as Noodweer. This study uses a type of normative research. The data collection method used in this research is library research. The source of the data in this study is secondary data, namely data obtained indirectly from the source from literature studies that have a relationship with the research object taken in the protection of robbery victims in perforce reviewed. Noodweer is used as a justification, but not as a reason to justify an unlawful act, but rather someone who is forced to commit a crime is forgiven because there was a violation of the law that preceded the act. The causal relationship between attack and mental shock is perforce reviewed, and cannot eliminate the nature of breaking the law, but in conditions of mental shock, it can be a justifying reason or excuse that can abolish the punishment. Legislators must provide more detailed explanations of the articles so that they are more easily understood by the public, besides that it is hoped that there will be an update from the colonial Criminal Code into a new law. In addition, law enforcement officials must be able to pay more attention to the problem of victims with dual status so that legal protection for victims with dual status gets clarity about the rights they deserve.